Application of Condition Index to Evaluate Environmental Health of Fishes: A Case Study With Labeo Rohita (Bangladesh Journal of Zoology, 2023)
We monitored the Condition Index (CI) of Labeo rohita, which is an important indicator to evaluate the health and well-being of the cultured fish. In this pilot project, we initiated the culture with Labeo rohita as a candidate species in 12 rain water stocked ponds at Diamond Harbour during March, 2022 to October, 2022 and computed monthly condition index considering the mean weight and length of the cultured species (n = 65 for each pond). Simultaneously we measured the relevant hydrological parameters like surface water temperature, Dissolved Oxygen (DO), surface water pH, dissolved NO3, PO4 and SiO3 for all the ponds. We observed significant positive correlations of CI with surface water temperature, DO, and surface water pH, and significant negative correlations with dissolved NO3 and PO4. The results reveal the use of CI of Labeo rohita as proxy to well-being of the species.Bangladesh J. Zool. 50(3): 309-319, 2022